Efektivitas Rebusan Daun Muntingia Calabura L Segar dan Kering sebagai Penurun Hiperglikemia pada Mencit - Hasma Hasma; Suryanita Suryanita (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Muntingia Calabura L is one of the plants that can reduce hyperglycemia which has an antioxidant effect. This effect is due to its high content of flavonoids that can inhibit the oxidation process. This study aims to determine the effectiveness of fresh and dry cherry leaves decoction in reducing hyperglycemia in mice (Mus-Musculus). The study used a laboratory-experimental design with a glucose induction method using 24 male mice divided into eight groups: positive control (metformin), negative control (aquadest), three groups of cherry leaves (fresh and dry) with a concentration of 5%, 10%, and 15%. Each group consisted of 3 male mice. The results showed that an effective decrease was in the positive control of metformin 113 mg/dl, following a 15% concentration in fresh leaves 88 mg/dl, and 15% dry leaves 79 mg/dl. The conclusion in this study was that there was no significant difference between the stew of fresh cherry leaves and dried cherry leaves. The decoction of fresh cherry leaves and dried cherry leaves were both effective in reducing mouse hyperglycemia at a concentration of 15%. It is suggested for further research to use fresh and dry cherry leaf extract samples using other methods.